2013
DOI: 10.1074/jbc.m112.440677
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor Receptor Like-1 (FGFRL1) Interacts with SHP-1 Phosphatase at Insulin Secretory Granules and Induces Beta-cell ERK1/2 Protein Activation

Abstract: Background: FGFRL1 has a unique intracellular domain predicted to inhibit intracellular signaling. Results: FGFRL1 localizes to pancreatic beta-cell insulin granules and enhances intracellular signaling, insulin content, and matrix adhesion. Signaling was reduced by mutation of the intracellular domain. Conclusion: Contrary to prediction, FGFRL1 enhances biological responses in these cells. Significance: This study reveals a novel mechanism of intracellular signaling regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 43 publications
(32 reference statements)
3
44
0
Order By: Relevance
“…HEAT-on-a-chip will also improve biochemical assays that require high transduction efficiency. For example, we previously showed fibroblast growth factor receptor-like 1 (FGFRL1) over-expression increases insulin production and insulin secretion in a murine beta-cell line 54 . We now plan to extend our findings to intact primary human islets to perform higher sensitivity insulin ELISA or conduct western immunoblot analysis on critical signalling pathways, given that both of these biochemical assays require high transduction efficiency to discern significant biological effects.…”
Section: Discussionmentioning
confidence: 99%
“…HEAT-on-a-chip will also improve biochemical assays that require high transduction efficiency. For example, we previously showed fibroblast growth factor receptor-like 1 (FGFRL1) over-expression increases insulin production and insulin secretion in a murine beta-cell line 54 . We now plan to extend our findings to intact primary human islets to perform higher sensitivity insulin ELISA or conduct western immunoblot analysis on critical signalling pathways, given that both of these biochemical assays require high transduction efficiency to discern significant biological effects.…”
Section: Discussionmentioning
confidence: 99%
“…Fgfrl1 was presumed to inhibit FGF signaling by sequestering ligand (Steinberg et al, 2010). However, new evidence suggests that Fgfrl1 facilitates FGF liganddependent MAPK activation (Silva et al, 2013). Further, Fgfrl1 also enhanced FGF-stimulated Erk1/2 activation, implicating a role in ligand-dependent signaling (Silva et al, 2013).…”
Section: Prox1 Regulates the Expression Of Fgfr3 Lctl And Fgfrl1mentioning
confidence: 99%
“…However, new evidence suggests that Fgfrl1 facilitates FGF liganddependent MAPK activation (Silva et al, 2013). Further, Fgfrl1 also enhanced FGF-stimulated Erk1/2 activation, implicating a role in ligand-dependent signaling (Silva et al, 2013). Intriguingly, Fgfrl1 also increases basal Erk1/2 phosphorylation independently of FGF ligand.…”
Section: Prox1 Regulates the Expression Of Fgfr3 Lctl And Fgfrl1mentioning
confidence: 99%
“…The FGFR family is generally composed of three extracellular ig-like domains, a transmembrane helical region and an intracellular tyrosine kinase domain. [8][9][10] Gerber et al 9 demonstrated that FGFRL1 may be a positive regulator of the FGF signalling pathway rather than a decoy receptor during renal development. 5 Therefore, FGFRL1 is widely considered to negatively regulate the FGF signalling pathway by combining extracellular ligand to prevent its interaction with typical receptors.…”
Section: Introductionmentioning
confidence: 99%
“…However, FGFRL1 lacks the classic tyrosine kinase regions and contains a peculiar histone-rich region instead. 10 Recently, increasing evidence has shown that FGFRL1 plays a key role in many cancers, and overexpression of FGFRL1 has been associated with proliferation and metastasis of prostate and gastric cancer cells. Several studies have generated data supporting this hypothesis, 6,7 whereas others have found conflicting results.…”
Section: Introductionmentioning
confidence: 99%